IMPLEMENTASI E-SERVICE PADA ORGANISASI PUBLIK DI BIDANG PELAYANAN PUBLIK DI KELURAHAN CIBANGKONG KECAMATAN BATUNUNGGAL KOTA BANDUNG - Rd. Ahmad Buchari (Sosiohumaniora, 2016)
This research was done because the public demands a very large in the provision of services which provide information in accordance with the needs of the community. To answer this need the government to use information and communication technology called e-Government. E-Kelurahan is one kind of electronic services (e-Service) in the field of public service Bandung city. This study uses qualitative design wich focus on the problem how to implementing e-Service at the e-Kelurahan program funds what kind of obstacle. The results of this study show that the implementation of e-Service via e-Kelurahan has not been successful. This is evidenced by the existence of barriers that hinder the effectiveness and efficiency of e-Village program. Bandung City Government is expected to soon be providing professional executive personnel or by the holding of training for regional aggency of using the application in order to more effectively and efficiently.